Optical properties of advanced materials - Kajikawa, Kotaro; Aoyagi, Yoshinobu (Springer Series in Materials Science, 2013)
In the last decade, optically functionalized materials have developed rapidly, from bulk matters to structured forms. Now we have a rich variety of attractive advanced materials. They are applied to optical and electrical devices that support the information communication technology in the mid 21-th century. Accordingly, it is quite important to have a broad knowledge of the optical properties of advanced materials for students, scientists and engineers working in optics and related fields. This book is designed to teach fundamental optical properties of such advanced materials effectively. These materials have their own peculiarities which are very interesting in modern optical physics and also for applications because the concepts of optical properties are quite different from those in conventional optical materials. Hence each chapter starts to review the basic concepts of the materials briefly and proceeds to the practical use. The important topics covered in this book include:  quantum structures of semiconductors, spintronics,  photonic crystals, surface plasmons in metallic nanostructures, photonic metamaterials, liquid crystal materials, organic LED materials and magnet-optics.